Factors Influencing Tax Avoidance in Non-Financial Multinational Companies in Indonesia - Nisa Nabila; Y. Anni Aryani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of transfer pricing, fixed assets intensity, and sales growth on tax avoidance practices. This research focuses on non-financial multinational companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Tax avoidance is the dependent variable, while transfer pricing, fixed assets intensity, and sales growth are independent variables. The control variables used are profitability, leverage, and firm size. Purposive sampling is used as a sampling method. The sample in this study consists of 130 observational data from 26 non-financial multinational companies listed on the IDX in 2018-2022. The analysis method used is panel data regression with EViews 12 statistical test. The results of this study indicate that transfer pricing has a negative influence on tax avoidance. Sales growth has no impact on tax avoidance. Fixed asset intensity has a positive influence on tax avoidance. This study also shows that the control variables profitability and firm size affect tax avoidance, while leverage does not affect tax avoidance. This research is relevant for academics, researchers, and regulators. Examining transfer pricing, fixed assets intensity, and sales growth to tax avoidance can be a consideration for regulators, in this case, the Director General of Taxes to take action regarding companies that take advantage of loopholes in tax regulations.